PROCESS SIGNAL RESPONSE OF JOINING THIN MATERIAL AA1100 USING BOBBIN FRICTION STIR WELDING TECHNIQUE - Mohd Kassim, M.K.A.; Sued, M.K.; Hussein, N.I.S.; Aoh, J.N. (Journal of Advanced Manufacturing Technology (JAMT), 2022)
There are limited investigations of welding thin material focusing on process signal response and relate it to the welding parameter especially the AA1100. The AA1100 is known as difficult to weld using the fusion method because high Aluminum content. In this study, a thin material of AA1100 was joint using bobbin friction stir welding. The range of rotational and welding speed parameters were 1500-1600 rpm and 150-210 mm/min, respectively. The runs were arranged based on response surface method Box-Behnken design. There were 13 runs were conducted. During the process, four responses were recorded that were temperature, vibration, current supply and force. The weld specimens were tested for tensile, microhardness and observed under the Scanning Electron Microscope. Based on the data recorded, it found that the high harness and tensile was produced by 1550 rpm and 180 mm/min of rotational and welding speed. The welding speed was an important parameter in bobbin friction stir welding technique due to the heat generated was controlled by the welding speed. It is also found that the optimum welding temperature lied within 20.2-30.9% of melting point for the high strength joint. A pattern of an increased trend on the current measurement and measurement can be observed at a tool entry, which a valuable data for further study of the process setting like rigidity.